2012
DOI: 10.1586/erv.11.188
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for enhanced efficacy of DNA vaccines

Abstract: Despite many years of research, human DNA vaccines have yet to fulfill their early promise. Over the past 15 years, multiple generations of DNA vaccines have been developed and tested in preclinical models for prophylactic and therapeutic applications in the areas of infectious disease and cancer, but have failed in the clinic. Thus, while DNA vaccines have achieved successful licensure for veterinary applications, their poor immunogenicity in humans when compared with traditional protein-based vaccines has hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
228
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(236 citation statements)
references
References 215 publications
(200 reference statements)
3
228
0
5
Order By: Relevance
“…Furthermore, our study showed that the pCI-IL-6 co-immunized mice developed more potent cell-mediated immune responses, as evidenced by the higher levels of splenocyte IFN-γ production when re-stimulated with PAc. IFN-γ and IL-4 are Th1-type and Th2-type cytokines, respectively, and the former represents the cell-mediated immune response [35] , whereas the latter represents the humoral immune response [36] . Although the reason for Th1 biased T-cell induction rather than Th2 biased T-cell stimulation remains unknown, previous studies may partially explain the cause of T-cell differentiation after DNA vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study showed that the pCI-IL-6 co-immunized mice developed more potent cell-mediated immune responses, as evidenced by the higher levels of splenocyte IFN-γ production when re-stimulated with PAc. IFN-γ and IL-4 are Th1-type and Th2-type cytokines, respectively, and the former represents the cell-mediated immune response [35] , whereas the latter represents the humoral immune response [36] . Although the reason for Th1 biased T-cell induction rather than Th2 biased T-cell stimulation remains unknown, previous studies may partially explain the cause of T-cell differentiation after DNA vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of this type of technology is that it normally induces a Th2 type of response, at least in mice and in non-human primates [78]. Needle-free devices such as Biojector ® have also been developed and a more comprehensive review of this technology can be found in [79].…”
Section: Phase I Nct01922284mentioning
confidence: 99%
“…Besides the substances discussed previously, chemokines, signaling and co-stimulatory molecules have also been tested and a very detailed review is available in [79].…”
Section: Adjuvantsmentioning
confidence: 99%
“…Moreover, the production costs are relatively low, and the DNA is stable and does not require refrigeration for storage. 20,21 Several DNA vaccine formulations containing the F, G and matrix protein (M2) either alone or in combination were tested in animal models.…”
Section: Introductionmentioning
confidence: 99%